Feasibility of using half-dose Gd-BOPTA for delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) at the knee, compared with standard-dose Gd-DTPA - Rehnitz, Christoph; Do, Thuy; Klaan, Bastian; Burkholder, Iris; Barié, Alexander; Wünnemann, Felix; Kauczor, Hans-Ulrich; Weber, Marc-André (Journal of magnetic resonance imaging, 2020)
Background We sought to replace full-dose Gd-DTPA with safer and lower-dose contrast agents for delayed gadolinium-enhanced MRI of cartilage (dGEMRIC). Gd-BOPTA has a lower intrinsic nephrogenic systemic fibrosis risk and a 2-fold higher relaxivity at 3T; thus, the contrast agent dose may be halved, further reducing contrast agent-dependent risks. Purpose To compare the feasibility of using half-dose, high-relaxivity Gd-BOPTA vs. standard-dose Gd-DTPA for dGEMRIC. Study Type Prospective observational study. Subjects Eleven healthy volunteers (five women, mean age 25.7 years) and 10 patients with knee pain (three women, mean age 36.7 years; nine with chondromalacia). Field Strength/Sequences 3D T1-weighted volumetric breath-hold examination (VIBE) sequence at 3T. Assessment Knee dGEMRIC was performed twice, first using 0.1 mmol/kg Gd-BOPTA and 4 weeks later using 0.2 mmol/kg Gd-DTPA. Contrast penetration was studied using pre- and 60-120-min postcontrast imaging in volunteers and pre- and 90-min postcontrast imaging in patients. Femoral cartilage lesions were assessed using modified whole-organ MRI scores. Healthy cartilage and partial-thickness lesions were compared using region-of-interest analyses by independent readers. Statistical Tests Linear mixed-effect-models, area under receiver-operating-characteristic curve (AUC) analysis, intraclass correlation (ICC). Results In healthy volunteers, Gd-BOPTA and Gd-DTPA T1-values did not differ significantly at any timepoint (P = 0.164-0.995). In patients, Gd-BOPTA T1-values (743.33 ± 72.015 msec) were higher than Gd-DTPA T1-values (681.24 ± 67.635 msec, P = 0.030). Gd-BOPTA and Gd-DTPA detected chondromalacia areas equally well, with significantly lower T1-values than in healthy cartilage (P < 0.001) and nonsignificantly different AUCs (0.92 and 0.96, P = 0.27). The absolute decrease in T1-values between healthy and pathological cartilage was similar (Gd-BOPTA: 149.59 msec; Gd-DTPA: 149.44 msec, P = 0.99). ICCs were 0.83-0.98 for Gd-BOPTA and 0.80-0.98 for Gd-DTPA. Data Conclusion Gd-BOPTA might be used at half the Gd-DTPA dose in dGEMRIC, with similar contrast penetration and T1-values in healthy cartilage and noninferior detection of cartilage damage. Level of Evidence: 2 Technical Efficacy: Stage 5 J. Magn. Reson. Imaging 2020;51:144-154.